Технічні аспекти створення електронної музичної композиції - Бабак, К. В. (ХНУРЕ, 2023)
The audio production process consists of three main stages: recording, mixing, and mastering. At the moment, there is no detailed description of all the stages of compilation and mastering of a musical piece. Often, treatment descriptions contain a lot of subjective information in the complete absence of technical data, structural diagrams that help to understand the essence and result of treatments. The purpose of this work is to create a finished audio composition with a detailed technical and creative description of all stages of its recording, mixing and mastering
Keywords: музична композиція